CERVICOFACIAL CELLULITIS MANAGEMENT: A Review of 136 Cases - SAYAD, ZAHRA; NAJWA BELHAJ; Pr. S. NITASSI; Pr. R. BENCHEIKH; Pr. A. OUJILAL; Pr. M.A. BENBOUZID; Pr. S. BENAZZOU; Pr. L. ESSAKALLI; Pr. M. BOULAADAS (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
Our work aims to study the epidemiology and paraclinical profile of our patients, to evaluate their therapeutic management and their evolution. We included 136 patients treated between January 2018 and January 2020. Our series regains a male predominance of 72.6%. Dental origin is the most common etiology. CT scans with contrast product injection are the key examination of the initial balance sheet. Antibiotic therapy and surgery have allowed a good evolution. Cervicofacial cellulitis is a potentially serious condition, often affecting young adults whose hospital mortality must be reduced if it is diagnosed early and given immediate medical-surgical management.